The impact of oral nutritional supplementation in children treated for cancer - Feza Kırbıyık (Journal of Surgery and Medicine, 2021)
Background/Aim: Malnutrition is a dangerous comorbidity in children with cancer that can affect tolerance to treatment modalities such as chemotherapy and radiotherapy. It also adversely affects the treatment outcome and overall survival. It has been known that low Z score of body mass index (BMI) indicates malnutrition. This study aims to underline the effects of oral nutritional supplementation (ONS) on pediatric oncology patients. Methods: All records were collected from Kocaeli University Hospital, Department of Pediatric Oncology, Kocaeli, Turkey, and analyzed. Weight, height, and BMI status of sixty patients who received ONS with cancer treatment were recorded during visits up to 8 months after the start of ONS. Statistical analyses were maintained on the whole cohort as well as on following tumor sub-groups: CNS tumors (13.3%), lymphoma (18.3%), other tumors (68.3%). Results: Sixty malnourished pediatric oncology patients (64.6% male, 35.4% female) were included in the study cohort. BMI values of the majority (60%, P